2020
DOI: 10.1007/s00586-020-06397-5
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of 3D acetabular and lower limb parameters in adolescent idiopathic scoliosis

Abstract: Purpose To evaluate the 3D deformity of the acetabula and lower limbs in subjects with adolescent idiopathic scoliosis (AIS) and their relationship with spino-pelvic alignment. Methods Two hundred and seventy-four subjects with AIS (frontal Cobb: 33.5° ± 18° [10°-110°]) and 84 controls were enrolled. All subjects underwent full-body biplanar X-rays with subsequent 3D reconstructions. Classic spino-pelvic and lower limb parameters were collected as well as acetabular parameters: acetabular orientation in the 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Karam et al reported three-dimensional deformity of the acetabulum with AIS, as follows: The acetabulum was more abducted at the lower side vs upper side, the acetabulum was anteverted, and there was a lack of anterior coverage. These alterations were related to pelvic obliquity [ 29 ]. Therefore, to reduce the effect of pelvic obliquity as much as possible, the radiographic methods were standardized, and cases unsuitable for measurement of acetabular parameters because of pelvic rotation or pelvic lateral inclination were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Karam et al reported three-dimensional deformity of the acetabulum with AIS, as follows: The acetabulum was more abducted at the lower side vs upper side, the acetabulum was anteverted, and there was a lack of anterior coverage. These alterations were related to pelvic obliquity [ 29 ]. Therefore, to reduce the effect of pelvic obliquity as much as possible, the radiographic methods were standardized, and cases unsuitable for measurement of acetabular parameters because of pelvic rotation or pelvic lateral inclination were excluded.…”
Section: Discussionmentioning
confidence: 99%